Mechanisms of the different DNA adduct forming potentials of the urban air pollutants 2-nitrobenzanthrone and carcinogenic 3-nitrobenzanthrone - Stiborová, Marie; Martínek, Václav; Svobodová, Martina; Sístková, Jana; Dvorák, Zdenek; Ulrichová, Jitka; Simánek, Vilím; Frei, Eva; Schmeiser, Heinz H; Phillips, David H; Arlt, Volker M (Chemical research in toxicology, 2010)
2-Nitrobenzanthrone (2-NBA) has recently been detected in ambient air particulate matter. Its isomer 3-nitrobenzanthrone (3-NBA) is a potent mutagen and suspected human carcinogen identified in diesel exhaust. We compared the efficiencies of human enzymatic systems [hepatic microsomes and cytosols, NAD(P)H:quinone oxidoreductase 1 (NQO1), xanthine oxidase, NADPH:cytochrome P450 reductase, N,O-acetyltransferases, and sulfotransferases] and human primary hepatocytes to activate 2-NBA and its isomer 3-NBA to species forming DNA adducts. In contrast to 3-NBA, 2-NBA was not metabolized at detectable levels by the tested human enzymatic systems and enzymes expressed in human hepatocytes, and no DNA adducts detectable by (32)P-postlabeling were generated by 2-NBA. Even NQO1, the most efficient human enzyme to bioactive 3-NBA, did not activate 2-NBA. Molecular docking of 2-NBA and 3-NBA to the active site of NQO1 showed similar binding affinities; however, the binding orientation of 2-NBA does not favor the reduction of the nitro group. This was in line with the inhibition of 3-NBA-DNA adduct formation by 2-NBA, indicating that 2-NBA can compete with 3-NBA for binding to NQO1, thereby decreasing the metabolic activation of 3-NBA. In addition, the predicted equilibrium conditions favor a 3 orders of magnitude higher dissociation of N-OH-3-ABA in comparison to N-OH-2-ABA. These findings explain the very different genotoxicity, mutagenicity, and DNA adduct forming potential of the two compounds. Collectively, our results suggest that 2-NBA possesses a relatively lower risk to humans than 3-NBA.
Keywords: karcinogeny; Liver; kultivované buňky; Hepatocytes; játra; látky znečišťující vzduch; isomerie; Air Pollutants; Computer Simulation; benz(a)anthraceny; počítačová simulace; DNA Adducts; NAD(P)H Dehydrogenase (Quinone); NAD(P)H dehydrogenasa (chinon); Cells, Cultured; hepatocyty; Humans; Binding Sites; Carcinogens; Catalytic Domain; Benz(a)Anthracenes; adukty DNA; katalytická doména; Isomerism; vazebná místa; lidé